Predictive Value of Neutrophil to Lymphocyte Ratio in Clinical Outcomes of Non-ST Elevation Myocardial Infarction and Unstable Angina Pectoris A 3-Year Follow-Up - Gul, Mehmet; Uyarel, Huseyin; Ergelen, Mehmet; Ugur, Murat; Isik, Turgay; Ayhan, Erkan; Turkkan, Ceyhan; Aksu, Hale Unal; Akgul, Ozgur; Uslu, Nevzat (My University, 2014)
We sought to determine the prognostic value of neutrophil to lymphocyte ratio (NLR) in non-ST elevation myocardial infarction (NSTEMI) and unstable angina pectoris (UAP). A total of 308 (mean age 59.22 +/- 11.93) patients with NSTEMI and UAP were prospectively evaluated. The study population was divided into tertiles based on admission NLR values. The patients were followed for clinical outcomes for up to 3 years after discharge. In the Kaplan-Meier survival analysis, 3-year mortality was 21.6% in patients with high NLR versus 3% in the low-NLR group (P 3.04 yielded a sensitivity of 79% and specificity of 71%. Admission NLR is the strong and independent predictor of a 3-year cardiovascular mortality in patients with NSTEMI and UAP.